Expansion of Functions and Role of Mediators in Polygamy Permit Cases to Enforce the Principles of Monogamy - Alhadiansyah Alhadiansyah; Angga Prihatin; Sugeng Susila (International Journal Labs, 2026)
Indonesian marriage law adheres to the principle of non-absolute monogamy, allowing polygamy with religious court permission. Although polygamy permit cases are categorized as disputes requiring mandatory mediation, mediation becomes unnecessary when both husband and wife have mutually agreed to the polygamy, as no actual dispute exists. In such situations, the mediation process risks overriding the principle of monogamy. The purpose of this article is to conduct a legal analysis of the implementation of mediation of polygamy permit applications in religious courts and to find solutions to uphold the application of the principle of monogamy at the mediation stage of polygamy permit applications. This article employs a normative juridical method, namely a study of the principles and norms in statutory regulations with an analytical approach, by analyzing legal materials to ascertain the meaning contained in the terms used in statutory regulations conceptually. The results of this research show that in polygamy permit applications where there is no dispute between the parties, the role of the mediator needs to be expanded to act as a negotiator to prioritize the principle of monogamy, as well as to prevent polygamy permit applications that are not in accordance with legal provisions from continuing in the examination process, as an implementation of the principles of administering justice that are simple, fast, and low-cost.